O Programa de Pós-Graduação em Educação Profissional e Tecnológica do IFSP: contribuições na perspectiva de seus participantes - Lemes, Fernanda Cristina Gaspar (Universidade Federal de São Carlos, 2020)
In the year of 2017, the Federal Institute of Education, Science and Technology of São Paulo (IFSP) was linked to the Mestrado Profissional em Educação Profissional e Tecnológica em Rede Nacional (Professional Master’s Degree in Professional and Technological Education in a National Network) (ProfEPT). Considering this scenario, the present investigation aims to understand – from the perspective of the civil servants who attended the first class of ProfEPT-IFSP – in what ways the master’s degree can contribute to their performance and professional development. A study of the documentation that regulates and guides both ProfEPT and ProfEPT-IFSP was carried out, and the objective of the study is understanding how the Programa de Mestrado Profissional em Rede (a Professional Master’s Program that works as a network) is constituted, as well as identifying and analyzing its conceptions and formative perspectives. This study also presents a historical contextualization of the Professional Master’s programs in the country, portraying the proposals, needs and initiatives that started and allowed the development of these programs in the context of the stricto sensu Post-Graduation in Brazil, also addressing how the Professional Master’s related to Education was founded/created in Brazil. The investigative design aims to enable the participants to present their conceptions and personal perspectives on the theme of the investigation of this study. Questionnaires were used for the construction of the personal and professional profile of the participants, as well as the online interviews focused on the training process and development of the work of these participants as masters of the ProfEPT-IFSP. An interview with the Program’s coordinator was conducted, aiming to understand the management’s opinion about the first professional master’s class and the results achieved. In the theoretical framework there are included studies that study aspects of learning, the reflective processes, professional identity and professional development of teachers in a more specific way; and what differs this investigation from others is that it also investigates aspects related to the learning and professional development of others educational agents, in this case the IFSP civil servants who were part of the first class of ProfEPT-IFSP. The results from the analysis and the systematization of the data show that, from the perspective of the participants – and also of the Program’s management – ProfEPT-IFSP generated learning and promoted reflections that influence the process of consolidating the professional identity and professional development of the civil servants that participated in this investigation. Therefore, they say that the main thing they’ve learned (related to the program) was developing a deeper understanding of Professional and Technological Education, its historical path, and its theoretical foundation as a teaching modality that aims at the social transformation and the emancipation of its students. Such understanding resulted in having a greater knowledge about the institution in which they work at and the role they play in it as civil servants, which is a necessary element for their professional development. There was also evidence of learning related to the professional performance of these employees when they made it clear that they felt more qualified to perform their duties. Also during the data analysis process it was possible to understand, from the perspective of the interviewed participants, some limitations of the ProfEPT-IFSP, or aspects that could be rethought in order to improve the Program. Such aspects are related to the conceptual alignment of a minority of the program’s teachers, not only regarded to the conceptual bases of Professional and Technological Education, but also related to the design of educational products that need to be developed to complete the program.
Programa de Posgrado de Educación Profesional y Tecnológica IFSP: contribuciones desde la perspectiva de sus participantes
The Postgraduate Program in Professional and Technological Education at IFSP: contributions from the perspective of its participants
Keywords: Desenvolvimento profissional; Aprendizagem profissional; Mestrado profissional em ensino; Educação profissional e tecnológica; Professional development; Learning professional; Professional master’s education; Professional and technological education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO